2011
DOI: 10.1007/s11240-011-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphohistological and flow cytometric analyses of somatic embryogenesis in Trifolium nigrescens Viv.

Abstract: Microscopy and flow cytometry (FCM) were used to study somatic embryogenesis (SE) from zygotic embryos of Trifolium nigrescens Viv. to determine if there were any relationships between characteristics of somatic embryos (morphology, anatomy, genome size stability) and their regenerability. Embryoids were induced on Murashige and Skoog (MS) medium containing 4 mg l -1 2,4-dichlorophenoxyacetic acid (2,4-D) and 2 mg l -1 N 6 -[2-isopentenyl]-adenine (2iP) either directly from hypocotyls or via an intervening cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…However, two distinct groups of cells were observed: one was formed of large, non-embryonic cells at the periphery of the explants; the other group was localized more centrally and composed of small cells with a meristematic appearance. The same structural pattern was observed by Konieczny et al (2012) during the somatic embryogenesis of Trifolium nigrescens Viv.…”
Section: Histological and Structural Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…However, two distinct groups of cells were observed: one was formed of large, non-embryonic cells at the periphery of the explants; the other group was localized more centrally and composed of small cells with a meristematic appearance. The same structural pattern was observed by Konieczny et al (2012) during the somatic embryogenesis of Trifolium nigrescens Viv.…”
Section: Histological and Structural Analysissupporting
confidence: 78%
“…The occurrence of abnormalities during the embryogenic process is common (Fernando et al 2002, Konieczny et al 2012. It has been suggested that these abnormalities are associated with the culture duration and the use of high auxin concentrations (Pescador et al 2008).…”
Section: Histological and Structural Analysismentioning
confidence: 99%
“…Conversely, branched and mostly parenchymatous outgrowths were prevalent in the control culture. Recently, we have observed that aberrant embryo morphology may be the prime cue for low conversion rate or even total inability to develop into plants after subculture on the regeneration media (Konieczny et al 2012). Interestingly, the anthers-derived calli of barley cultured in the presence of gum arabic showed a significantly higher ability to regenerate plants relative to calli maintained without gum arabic.…”
Section: Discussionmentioning
confidence: 98%
“…Š amaj et al (1995) and Bobák et al (2003/4) suggested that the formation of an ECMSN can be a stress response of the explants imposed by specific in vitro conditions. Previously, we found that the incidence of both morphological abnormalities and genetic instability in SE of T. nigrescens increased with time of culture (Konieczny et al 2012). It may not be ruled out, that occurrence of ECMSN at relatively late stages of culture (around 15 days after explantation), could be a result of prolonged exposure to unfavorable culture conditions.…”
Section: Structure Of the Ecmsnmentioning
confidence: 91%